Fit accuracy and fracture resistance evaluation of advanced lithium disilicate crowns (in- vitro study) - Amro Khalil Fayed; Amir Shoukry Azer; Rewaa Gaber AboElhassan (BMC Oral Health)
Abstract Background Increasing demand for durable and aesthetically pleasing dental restorations, including laminates, inlays, onlays, and crowns, has led to advancements in all-ceramic systems, particularly with the development of advanced lithium disilicate materials. However, limited data on the fit accuracy and fracture resistance of these materials restricts their wider application in clinical restorative practices. Aim of the study This in vitro study aims to compare the marginal and internal fit, assess the fracture resistance, and evaluate the failure modes of crowns fabricated from advanced and conventional lithium disilicate materials. Materials and methods Thirty two (n = 32) crowns were fabricated and categorized into two groups based on the material used: Group (CT), where crowns were milled from CEREC Tessera (n = 16), and Group (EM), where crowns were milled from IPS e.max CAD (n = 16) using a CAD/CAM system. The marginal and internal fit were assessed digitally via a triple scan protocol. All samples were subjected to a fracture resistance test with a universal testing machine, followed by an analysis of failure modes under a stereomicroscope. Results In the evaluation of marginal, internal and total gaps, CEREC Tessera (CT) showed slightly better fit with lower gap values compared to e.max CAD (EM). However, an independent samples t-test indicated no statistically significant differences between the two groups (p = 0.141, p = 0.471). For fracture resistance (N), the CT group demonstrated higher values than the EM group; however, the independent samples t-test indicated no statistically significant difference (p = 0.053). Additionally, the Chi-squared test with Monte Carlo correction revealed no statistically significant differences in the modes of fracture between the two groups (p = 0.484). Conclusion Considering the limitations of this study, advanced lithium disilicate crowns demonstrated better results in terms of marginal fit, internal adaptation, and fracture resistance compared to traditional lithium disilicate crowns; however, the differences were not statistically significant. Both materials exhibited comparable fracture patterns.